2023
DOI: 10.1186/s40359-023-01264-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychosocial factors associated with quality of life in patients with head and neck cancer: an analytical cross-sectional study from a lower-middle-income country

Nida Zahid,
Russell Seth Martins,
Zaiba Shafik Dawood
et al.

Abstract: Introduction The disease course of head and neck (H&N) cancer can severely impair patients’ quality of life (QoL). In Pakistan, a South Asian lower-middle-income country (LMIC), psychosocial factors may impact QoL. We aimed to assess QoL and associated factors amongst patients with H&N cancer in Pakistan. Methods An analytical cross-sectional study was conducted amongst adult (≥ 18 years) patients with H&N cancer who were ≥ 4 weeks post… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…These findings were consistent with a study conducted to evaluate the OHRQoL using the OHIP tool, which reported a significant difference in the OHRQoL score in patients with varying degrees of oral mucositis compared to patients without it 26 Nevertheless, it is noteworthy that 52% of the patients experiencing moderate to severe OM symptoms had concluded their cancer treatment over six months ago. This finding is unexpected, given the studies have reported that symptoms of OM typically abate or become mild within a three-month period following cancer treatment 19 , 36 . A significant association between the oral mucositis severity and use of fluoride was also observed, suggesting improvement in the OHRQoL due to decrease in the severity of mucositis by the use of fluoride toothpaste, this is also supported by 37 which recommended that the use of high fluoride tooth paste, fluoride gel or fluoride mouthwash prescribed to patients during and after their cancer treatment could reduce the severity of mucosal inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…These findings were consistent with a study conducted to evaluate the OHRQoL using the OHIP tool, which reported a significant difference in the OHRQoL score in patients with varying degrees of oral mucositis compared to patients without it 26 Nevertheless, it is noteworthy that 52% of the patients experiencing moderate to severe OM symptoms had concluded their cancer treatment over six months ago. This finding is unexpected, given the studies have reported that symptoms of OM typically abate or become mild within a three-month period following cancer treatment 19 , 36 . A significant association between the oral mucositis severity and use of fluoride was also observed, suggesting improvement in the OHRQoL due to decrease in the severity of mucositis by the use of fluoride toothpaste, this is also supported by 37 which recommended that the use of high fluoride tooth paste, fluoride gel or fluoride mouthwash prescribed to patients during and after their cancer treatment could reduce the severity of mucosal inflammation.…”
Section: Discussionmentioning
confidence: 89%